O3-S4.02 Is single dose azithromycin adequate for asymptomatic rectal chlamydia?. (10th July 2011) - Drummond, F; Ryder, N; Wand, H; Guy, R; Read, P; McNulty, A; Wray, L; Donovan, B
Abstract : Background: Azithromycin is the recommended first-line therapy for asymptomatic rectal chlamydia. However a recent European study reported significant numbers of treatment failures, with higher failure rates in HIV positive men. In 2009, the Sydney Sexual Health Centre instituted a 6 week re-test policy for all cases of asymptomatic rectal chlamydia to assess the extent of azithromycin treatment failures. Methods: We conducted a retrospective audit of all men who have sex with men (MSM) diagnosed with asymptomatic rectal chlamydia in 2009. MSM with anal symptoms were excluded from this analysis, due to the possibility of lymphogranuloma venereum. We then categorised the infections present at re-testing as probable re-infections (men reported ongoing sexual activity with an untreated partner) or probable treatment failures (men did not have any obvious ongoing exposure, either because they did not report any further anal sex with any existing partners or because condoms were used consistently with all partners). Results: In the 12-month period there were 116 asymptomatic MSM treated for rectal chlamydia with 1 gram azithromycin as a single dose. Fourteen (12%) of the men were HIV positive. The median age was 33 years (range 20–64 years). Of the 116 men, 85 (73%) returned at varying times; median time of 10 weeks (78 days, range 21–372 days. Of the 85 men who returned, 11 (13%) were persistently positive and the median time to re-test was 11 weeks (78 days, range 47–209 days). Six of the 11 men were classified as probable re-infection and five as probable treatment failures, equating to an efficacy of 94%. None of the men classified as probable treatment failures were HIV positive. Conclusions: Interpreted conservatively, the azithromycin treatment failure rate could have been as high as 13% in our study. However most of these cases could be explained by re-infection suggesting an actual treatment failure rate of 6%. There was no evidence azithromycin is an ineffective first-line therapy for asymptomatic rectal chlamydia in MSM, but prospective studies would be welcome.